A Crisis of Governance – Or an Opportunity?. (July 2021) - Areal, Andreia G.; Sheppy, Bruce
The National Health Service Track and Trace Programme has been one of the most pivotal and controversial tools the UK government has deployed to combat the COVID-19 pandemic. This article reviews the challenges of the development and implementation of the NHS COVID-19 mobile application, and reviews these in the context of the following 3 key areas: outsourcing of public sector, organisational structure and leadership, digital framework and governance. The paper argues that the current pandemic has demonstrated weaknesses in each of the above-mentioned areas, and that is an urgent need to strategically address these in order to prepare for the next public health crisis.